The use of hypnotic communication in PICC placement: randomized controlled trial study - Monolo, Davide; Barisone, Michela; Cordio, Giuseppe; Della Sanità, Marco; Airoldi, Chiara; Radrizzani, Danilo; Bassi, Erika; Dal Molin, Alberto; Gallione, Chiara (The American journal of clinical hypnosis, 2024)
Every time a patient undergoes a medical procedure, unpredicted personal stress occurs. According to the available literature, the hypnotic communication technique has been used to reduce stress and pain during several major invasive procedures. The primary goal of this study was to compare the effectiveness of hypnotic communication combined with buffered Lidocaine, versus buffered Lidocaine alone, on patients' negative emotions while undergoing Peripherally Inserted Central Venous Catheter (PICC) placement. Secondary aims were evaluating patients' pain, satisfaction, and procedure timing and costs. A randomized controlled trial was conducted in an Italian Hospital involving patients who needed a PICC, with any disease or condition, aged over 18, cognitively oriented, able to hear, and willing to give consent. Emotional assessment was performed using the Emotion Thermometer Tool. Sixty-seven subjects were enrolled: 17 refused to participate, and 25 were randomly assigned to each group. The results showed a statistically significant higher decline in the total Emotion Thermometer Tool score for the experimental group using hypnotic communication. A significant mean reduction in anger and depression was also observed, while both groups reported low levels of perceived pain. Hypnotic communication appears to be a successful method for reducing emotional stress during PICC placement. However, further research is needed to determine the relationship between hypnotic communication, emotional distress, and pain perception in patients undergoing central vascular catheter insertion.